Testing the effect of descriptive dynamic social norm messages on meatless food purchases in Aotearoa New Zealand and UK university food outlets - Patel, Vibhuti; Mirosa, Miranda; Buckland, Nicola J. (Frontiers in Sustainable Food Systems, 2024)
A reduction in meat consumption is urgently needed to address multiple harms related to the environment, animal welfare, and human health. Social norm interventions have been found to be feasible and effective at shifting consumer behaviour, however, evidence related to meat reduction behaviour is limitedespecially in naturalistic settings. Two social norm interventions were conducted at university food outlets in Aotearoa New Zealand and in the UK, to assess the effect of social norm messages on meat and meatless food purchases. Both interventions consisted of a weeklong intervention phase during which descriptive dynamic social norm messages referring to reduced meat intake were displayed in the food outlets (study one and two) and via social media (study two). Meat and meatless food purchases during the interventions were compared to pre-and postintervention weeks. Surveys were also conducted with a sub-group of customers to assess demographics, dietary habits, and awareness of the social norm message. In both studies, there was no significant effect of the social norm interventions on meat or meatless food purchases, and awareness of the norms message across both studies was low. These findings indicate that social norm interventions alone may be ineffective in encouraging meat reduction. Implications for interventions to reduce meat intake to support pro-environmental food choices are discussed.